Pengaruh Fundamental Mikro, Profitabilitas Terhadap Nilai Perusahaan Dengan Struktur Kepemilikan, Struktur Modal sebagai Variabel Intervening di Perusahaan BEI - Diah Indri Anggriyanti; Hwihanus Hwihanus (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
The purpose of this study is to analyse the effect of Micro Fundamentals (X1) and Profitability (X2) on firm value with Ownership Structure (Z1) and Capital Structure (Z2) as intervening variables in companies listed on the Indonesia Stock Exchange (IDX). The independent variables used are micro fundamentals with indicators of DR, LDR, and DCR, and profitability with indicators of GPM, NPM, and ROE. Intervening variables include ownership structure (Type of Ownership, Type of Shareholders, Number of Board of Commissioners) and Capital Structure (Z2), namely (EBIT, LTDER, DAR). The dependent variable analysed is Firm Value (Y) which is measured using ROA, EPS, and PER. The research method uses quantitative methodology with secondary data consisting of company balance sheet reports during a certain period. The SmartPLS 4 application was used to conduct data analysis to test the relationship between variables. The study results prove that Micro Fundamental (X1) has no significant direct influence on Firm Value (Y), but has a significant influence on capital structure. Profitability (X2) has a significant effect on Firm Value (Y). Capital Structure (Z2) also plays a significant role as an intervening variable in the relationship between Micro Fundamental (X1) and Firm Value (Y). These findings provide important insights for company management and investors in managing financial structure to increase Firm Value (Y).